A Statistical Consideration Regarding the Threshold of the Psychopathy Checklist–Revised. Issue 5 (3rd September 2017) - Balsis, Steve; Busch, Alexander J.; Wilfong, Kevin M.; Newman, Joseph W.; Edens, John F.
ABSTRACT: The Psychopathy Checklist–Revised (PCL–R; Hare, 2003 ) is one of the most commonly used measures of psychopathy. Scores range from 0 to 40, and legal and mental health professionals sometimes rely on a cut score or threshold to classify individuals as psychopaths. This practice, among other things, assumes that all items contribute equally to the overall raw score. Results from an item response theory analysis (Bolt, Hare, Vitale, & Newman, 2004 ), however, indicate that PCL–R items differ in the amount of information they can provide about psychopathy. We examined the consequences of these item differences for using a cut score, detailing the consequences for a previously applied cut score of 30 as an example. Results indicated that there were more than 8.5 million different response combinations that equaled 30 and more than 14.2 million that equaled 30 or more. This raw score, like others, corresponded to a broad range of PCL–R-defined psychopathy, indicating that applying cut scores on this measure results in imprecise quantifications of psychopathy. We show that by using the item parameters along with an individual's particular scores on the PCL–R items, it is possible to arrive at a more precise understanding of an individual's level of psychopathy on this instrument.